Analysis of Students' Scientific Literacy Ability by the Implementation of Case Method Learning - Seprianto Seprianto; Hasby Hasby (Postgraduate, University of Mataram, 2023)
This study aims to analyze the increase in students' scientific literacy by implementation of case method learning. This is a quasi-experimental research using a one group pretest-posttest design. The research sample is the first semester students of the Chemistry Education Department at Universitas Samudra in the odd semester of the 2022/2023 academic year. This research consists of four stages, namely material analysis, development of tools and instruments, implementation, and data analysis. The scientific literacy test instrument was used to measure students' scientific literacy. Students' scientific literacy skills are presented according to content, science process, and context aspects. The increase in students' scientific literacy skills was analyzed based on the N-gain and paired sample t test. The results of the study found that students' scientific literacy skills in all content, science process, and contexts, were higher in the posttest than the pretest except for content energy that accompanies changes in material and context of natural resources. The average scientific literacy ability of students at the posttest (74.33) was higher than at the pretest (57.08). The N-gain value of 0.40 indicates an increase in students' scientific literacy skills with implementation of case method learning in the medium category. Analysis with paired sample t test indicates a significant difference in the pretest and posttest scores. Thus, it can be concluded that case method learning can improve students' scientific literacy skills in the three domains of scientific literacy.